A gradient structure biodegradable composite material and a preparation method thereof

CN122876754APending Publication Date: 2026-10-09SHOUKANG MEDICAL SCI & TECH (SHANDONG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611232259.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种梯度结构生物降解复合材料及其制备方法,解决了现有生物降解复合材料难以兼顾表面功能化与芯层轻量化、多层结构层间易剥离失效,以及复杂梯度微观结构无法连续规模化制备的问题

Benefits of technology

[0036]1、本发明通过在交替层叠的第一母粒与第二母粒中差异化引入偶氮二甲酰胺发泡剂与自成核调控剂,在厚度方向上构建了纤维含量、孔隙率和结晶度连续变化的梯度微观结构,使得材料兼具致密高结晶表层的优良表面功能(如耐刮擦、高阻隔)以及多孔低结晶芯层的轻量化缓冲特性,不仅使结晶度能够实现大跨度的连续调控,更使芯层密度降低并实现整体的减重,拓展了其在梯度地膜、包装膜及汽车轻量化内饰等领域的应用边界。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122876754A_ABST
    Figure CN122876754A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of biodegradable materials, and discloses a gradient structure biodegradable composite material and a preparation method thereof.The composite material is formed into a multi-layer structure by alternately stacking first master batches and second master batches, and has at least one gradient structure in fiber content, porosity and crystallinity in the thickness direction.The first master batch is mainly composed of a polyester matrix, bamboo fiber ultrafine powder, a dopamine modified polyethylene imine interface reinforcing agent, a self-nucleation regulator and azodicarbonamide, etc.The second master batch is mainly composed of a polyester matrix, bamboo fiber ultrafine powder and the interface reinforcing agent.During preparation, two master batch melts are subjected to multi-layer co-extrusion and layer multiplication treatment, and then the microstructure is shaped and locked by using an asymmetric gradient cooling system.The present application realizes on-demand customization and lightweight synergy of the performance of the composite material, has high interlayer bonding force, and breaks through the efficiency bottleneck of continuous and large-scale preparation of gradient composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biodegradable materials technology, specifically to a gradient structure biodegradable composite material and its preparation method. Background Technology

[0002] With the increasing severity of global plastic pollution and the advancement of the "dual-carbon" strategy, biodegradable materials have received widespread attention as alternatives to traditional petroleum-based plastics. Conventional biodegradable polyesters such as polylactic acid (PLA) and polybutylene adipate / terephthalate (PET) have already seen initial applications in packaging, agriculture, and interior decoration. However, single biodegradable polyesters often have inherent performance limitations, making it difficult to meet the diverse needs of complex application scenarios.

[0003] To overcome the shortcomings of single materials, existing technologies often employ component blending or multilayer composites for modification. However, traditional homogeneous composite materials have a uniform structure in the thickness direction, failing to simultaneously meet the contradictory requirements of surface densification and functionalization (such as high barrier and scratch resistance) and lightweight, energy-absorbing core layers. They also lack the ability to customize composite material properties on demand in the spatial dimension. Furthermore, in constructing multilayer composite systems, the differences in thermal shrinkage rates and poor compatibility between layers due to component variations often result in a lack of strong chemical covalent cross-linking networks at the macroscopic interlayer interfaces. This makes the materials highly susceptible to interlayer delamination failure during actual processing, service, or under stress, severely impacting the overall mechanical stability of the composite material. Moreover, to obtain complex three-dimensional microstructures, existing technologies often rely on cumbersome layer-by-layer bonding or multiple coating and assembly processes. It is difficult to achieve continuous distribution and precise morphological locking of large-span gradient layer structures during conventional polymer melt extrusion processes. This prevents the continuous production of such high-performance materials, and the low production efficiency severely hinders the large-scale preparation and industrial application of gradient structure composite materials. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a gradient structure biodegradable composite material and its preparation method, which solves the problems of existing biodegradable composite materials being unable to simultaneously achieve surface functionalization and core lightweighting, easy delamination failure between multilayer structures, and the inability to continuously and scalably prepare complex gradient microstructures.

[0005] To achieve the above objectives, the present invention provides the following technical solution: Firstly, the present invention provides a gradient structure biodegradable composite material, employing the following technical solution:

[0006] A gradient structure biodegradable composite material, wherein the biodegradable composite material is formed by alternating layers of a first masterbatch and a second masterbatch to form a multilayer structure, and has at least one gradient structure selected from fiber content gradient, porosity gradient and crystallinity gradient in the thickness direction;

[0007] The first masterbatch comprises the following raw materials in parts by weight: 58-99 parts polyester matrix; 0-40 parts bamboo fiber ultrafine powder; 0-2 parts dopamine-modified polyethyleneimine interface reinforcing agent; 0-3 parts self-nucleating regulator; 0-3 parts azodicarbonamide; and 0-2 parts nano-silica. The parts by weight of bamboo fiber ultrafine powder, self-nucleating regulator, and azodicarbonamide in the first masterbatch are not all 0 parts. The second masterbatch comprises the following raw materials in parts by weight: 89-100 parts polyester matrix; 0-10 parts bamboo fiber ultrafine powder; and 0-1 part dopamine-modified polyethyleneimine interface reinforcing agent.

[0008] By adopting the above technical solution, due to the use of first and second masterbatches with different component ratios, an asymmetric spatial distribution is constructed in the thickness direction using an alternating layered structure; due to the use of dopamine-modified polyethyleneimine interface reinforcing agent to connect bamboo fiber ultrafine powder and polyester matrix; and due to the use of self-nucleating regulator and azodicarbonamide to regulate the local crystallization behavior and foamed microporous structure of the material, a multifunctional biodegradable composite material with mechanical properties, buffering properties, and a continuously gradient change in degradation rate in the thickness direction is obtained.

[0009] Specifically, the interfacial crosslinking and structure regulation mechanism of the composite material of the present invention is as follows:

[0010] Step 1: The catechol groups in the dopamine-modified polyethyleneimine molecular chain form a dense hydrogen bond network with the active hydroxyl groups on the surface of bamboo fiber.

[0011] Step 2: The high-density amino groups in the dopamine-modified polyethyleneimine structure undergo an amidation reaction with the terminal carboxyl groups of the polyester matrix molecular chains at the melt processing temperature, forming covalent crosslinks. The interfacial reaction between the organic and inorganic phases significantly improves the interlayer peel strength and overall mechanical modulus.

[0012] Step 3: After the first masterbatch and the second masterbatch are stacked together, azodicarbonamide decomposes and releases gas. Nano-silica provides heterogeneous nucleation sites to control the pore size. The concentration difference between the components drives the bubble distribution to produce spatial hierarchy, thus completing the gradient regulation of porosity.

[0013] Preferably, the nucleation regulator is prepared by modifying the bamboo fiber ultrafine powder with a silane coupling agent, and the nucleation temperature for inducing polymer crystallization by the nucleation regulator is 125-135℃. The preparation method of the nucleation regulator includes: dispersing the bamboo fiber ultrafine powder in a sodium hydroxide aqueous solution with a mass fraction of 1%-3%, mechanically stirring it in a constant temperature water bath at 60-80℃ for 1-3 hours, filtering, washing and drying it; immersing it in a mixed solution containing 3-aminopropyltriethoxysilane and stirring for hydrolysis reaction for 2-4 hours, and then vacuum curing and drying to obtain the nucleation regulator; the particle size D50 of the bamboo fiber ultrafine powder is 5-20 μm, and the aspect ratio is 20-40.

[0014] By employing the above technical solution, the mechanism of the self-nucleation regulator is as follows: First, sodium hydroxide aqueous solution is used to wash away the hemicellulose and lignin components on the surface of bamboo fibers, increasing the specific surface area and fully exposing the natural cellulose hydroxyl groups; subsequently, 3-aminopropyltriethoxysilane undergoes hydrolysis and condensation reaction, coating the fiber surface with an organosilicon molecular layer. This coating, on the one hand, reduces the surface energy of bamboo fibers, improving their dispersion compatibility in polyester melt; on the other hand, it constructs a large number of heterogeneous nucleation sites. When the temperature is in the range of 125-135℃, the nucleation sites induce regular folding and stacking of polyester macromolecular chain segments, significantly increasing the crystallization rate and crystallization perfection of the matrix.

[0015] Preferably, the preparation method of the dopamine-modified polyethyleneimine interface enhancer is as follows: dissolving branched polyethyleneimine aqueous solution in a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0-8.5, adding dopamine hydrochloride, and reacting with mechanical stirring at 20-30°C in the dark for 12-24 hours. After dialyzing, the mixture is freeze-dried at -50°C to obtain the dopamine-modified polyethyleneimine interface enhancer; the dopamine grafting rate of the dopamine-modified polyethyleneimine interface enhancer is 8.0%-12.0%.

[0016] By employing the above technical solution, the tendency of dopamine hydrochloride oxidative self-polymerization is controlled in a pre-defined weakly alkaline buffer solution system. The primary and secondary amino groups on the branched polyethyleneimine molecular chains act as nucleophiles, undergoing Michael addition and Schiff base reactions with dopamine oxidation intermediates. Dialysis removes unreacted monomers and small molecule byproducts, while freeze-drying preserves the three-dimensional branched conformation of the modified polymer, ensuring that the grafting rate in specific regions provides sufficient interfacial binding active sites.

[0017] Preferably, the polyester matrix is ​​polylactic acid, poly(adipate adipate / butyl terephthalate), or a mixture of the two; when it is a mixture, the mass ratio of polylactic acid to poly(adipate adipate / butyl terephthalate) is (6-8):(2-4).

[0018] By adopting the above technical solution, the high strength modulus of polylactic acid and the high elongation at break of poly(adipate adipate / butyl terephthalate) achieve a rigid-flexible balance within the above mass ratio range, thus establishing a stable matrix continuous phase with a certain deformation capability.

[0019] Preferably, the raw materials of the first masterbatch are in the following weight parts: 75 parts polyester matrix, 20 parts bamboo fiber ultrafine powder, 2 parts self-nucleating regulator, 1.5 parts dopamine-modified polyethyleneimine interface reinforcing agent, and 1.5 parts azodicarbonamide; the raw materials of the second masterbatch are in the following weight parts: 99.5 parts polyester matrix and 0.5 parts dopamine-modified polyethyleneimine interface reinforcing agent; the biodegradable composite material is a three-dimensional gradient composite material, which simultaneously possesses the fiber content gradient, the porosity gradient, and the crystallinity gradient.

[0020] By adopting the above technical solution, the extreme concentration difference formed by the two specific masterbatches produces a three-dimensional synergistic effect. The dense, highly crystalline pure resin layer provides surface hardness and water-blocking performance, while the porous, high-fiber composite layer provides inner layer buffering, energy absorption, and structural support.

[0021] Secondly, the present invention provides a method for preparing a gradient structure biodegradable composite material, which adopts the following technical solution:

[0022] A method for preparing a gradient structure biodegradable composite material involves melting a first masterbatch and a second masterbatch prepared separately in an extruder, feeding the two melts into a multilayer co-extrusion distribution die to form an initial multilayer alternating fluid; sending the multilayer alternating fluid into a layer multiplier equipped with 1 to 5 cutting and stacking units for multiplication treatment, outputting a multiplied multilayer alternating melt; extruding the multiplied multilayer alternating melt through a wide-slit die, then entering a cooling system for cooling and shaping, and finally outputting and winding it up through a traction device to obtain the gradient structure biodegradable composite material; wherein, the cooling and shaping is performed by conventional cooling using a uniform temperature roller, or by asymmetric cooling using an independently temperature-controlled gradient cooling roller system; when performing asymmetric cooling, the temperature of the high-temperature side roller on one side of the thickness direction in the gradient cooling roller system is set to 80–135°C, and the temperature of the low-temperature side roller on the other side is set to 20–60°C.

[0023] By adopting the above technical solution, the asymmetric cooling process completes the solidification of macroscopic geometry and the locking of microscopic gradient structure. The specific evolution mechanism is as follows:

[0024] Step 1: When the melt is bonded to the asymmetric gradient cooling roller, a continuous and quantitative heat flux density difference is formed on both sides of the material thickness direction.

[0025] Step 2: The polymer melt layer near the high-temperature side roller cools and relaxes slowly, and the molecular chain segments retain sufficient internal rotational energy and movement space, allowing the crystallization thermodynamic process to continue. At the same time, the melt viscosity is moderate, and the foaming gas dissolved inside can expand smoothly to form large-sized bubbles, forming high-porosity, high-crystallinity micro-regions.

[0026] Step 3: The polymer melt layer near the low-temperature side roller is subjected to deep cryogenic quenching, and the conformational adjustment process of the polymer chain segments is frozen instantly, transforming into an amorphous amorphous state; at the same time, the local viscosity increases exponentially, and the strong melt strength inhibits the nucleation and growth of pores, forming a dense non-porous micro-region, which eventually solidifies into an asymmetric continuous gradient structure in the thickness direction.

[0027] Preferably, the melt blending and extrusion temperature of the first masterbatch and the second masterbatch in the extruder is controlled at 150-160°C.

[0028] By adopting the above technical solution, the matrix is ​​fully plasticized while avoiding the pyrolysis and carbonization of bamboo fiber and the premature and violent decomposition of foaming agent.

[0029] Preferably, the operating temperature of the layer multiplier is 150–165°C; and the number of layers of the output multilayer alternating melt is 10–200.

[0030] By adopting the above technical solution, the cutting and overlapping unit changes the rheological geometry of the fluid channel, controls the melt viscosity matching at a specific temperature, and ensures that the interlayer interface of the two fluids is clear and flat and does not break when undergoing channel recombination.

[0031] Preferably, the bamboo fiber ultrafine powder undergoes the following pretreatment process before being prepared into the masterbatch: natural moso bamboo is crushed and dried and then fed into a pulverizing system with a liquid nitrogen cooling jacket. The internal temperature of the pulverizing chamber is controlled at -65 to -55°C to induce low-temperature embrittlement in the glassy state. Subsequently, it is fed into a fluidized bed impingement jet mill and the classifying wheel speed is controlled at 2000 to 4500 rpm for ultrafine pulverization and collection.

[0032] By employing the above technical solution, the mechanism of liquid nitrogen cryogenic pretreatment is as follows: The temperature of the pulverizing chamber is lowered to -65 to -55°C, forcing the amorphous regions in the aggregated structure of natural cellulose to undergo a glass transition, causing the molecular chain segment movement to stagnate and resulting in low-temperature brittle fracture characteristics. Then, a high-speed impacting airflow is introduced, causing the brittle fibers to rapidly cleave and separate along the axial grain. This eliminates the accumulation of frictional heat generated by mechanical cutting and grinding, preserving the integrity of the crystalline regions at the microscale of bamboo fiber and its high aspect ratio, thus providing a high-quality rigid skeleton for the composite material.

[0033] Preferably, when the first masterbatch contains azodicarbonamide, the extrusion temperature of the wide-slit die is set to 165–170°C.

[0034] By adopting the above technical solution, the constant temperature window can accurately match the gasification plateau period of azodicarbonamide, so that the foaming agent can be concentrated in the wide-slit die head area to generate a homogeneous saturated gas solution, which provides foaming power for the subsequent depressurization expansion of the contact cooling roller.

[0035] This invention provides a gradient-structured biodegradable composite material and its preparation method. It possesses the following beneficial effects:

[0036] 1. This invention introduces azodicarbonamide foaming agent and self-nucleating regulator into the alternating layers of the first and second masterbatches to construct a gradient microstructure with continuously varying fiber content, porosity, and crystallinity in the thickness direction. This allows the material to possess both the excellent surface functions (such as scratch resistance and high barrier properties) of a dense, highly crystalline surface layer and the lightweight buffering properties of a porous, low-crystallinity core layer. This not only enables continuous control of crystallinity over a large range but also reduces the core layer density and achieves overall weight reduction, expanding its application boundaries in gradient mulch films, packaging films, and lightweight automotive interiors.

[0037] 2. This invention introduces a dopamine-modified polyethyleneimine interface reinforcing agent, which synergistically combines with high aspect ratio bamboo fiber ultrafine powder obtained through cryogenic cleavage with liquid nitrogen. This not only improves the dispersion compatibility of bamboo fiber in the polyester matrix through a dense hydrogen bond network, but also forms covalent chemical connections between the functional layer, the interface agent, and the functional layer at the macroscopic layer interface. This effectively resists the internal stress caused by the difference in shrinkage rates between different gradient layers, significantly improving the interlayer peel strength of the gradient composite material and endowing the material with extremely excellent structural integrity and mechanical stability.

[0038] 3. This invention adopts a multi-layer co-extrusion, layer multiplication, and asymmetric gradient cooling integrated molding process. It uses a layer multiplier to cut and stack multiple alternating melts multiple times to achieve continuous and stable extrusion of multi-level micro-nano structures. At the same time, combined with an independently temperature-controlled gradient cooling roller system, the foaming and crystallization behavior of each layer is precisely locked by the temperature gradient difference in the thickness direction. This not only solidifies the complex spatial gradient morphology, but also achieves continuous and large-scale preparation process compared with traditional layer assembly or coating processes, thus improving production efficiency. Attached Figure Description

[0039] Figure 1 This is a schematic diagram comparing the porosity distribution gradient in the thickness direction of the present invention with that of an embodiment and a comparative example.

[0040] Figure 2 This is a schematic diagram illustrating the multidimensional distribution of macroscopic mechanical properties in embodiments and comparative examples of the present invention;

[0041] Figure 3This is a schematic diagram of the distribution mapping of multidimensional functional indicators in the embodiments and comparative examples of the present invention. Detailed Implementation

[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0043] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0044] Polylactic acid, CAS: 26100-51-6, weight average molecular weight is 100,000;

[0045] Polybutylene adipate / terephthalate, CAS: 55231-08-8, weight average molecular weight is 90000;

[0046] Branched polyethyleneimine is a branched polymer containing primary, secondary, and tertiary amine structures. CAS: 9002-98-6, weight-average molecular weight is 10000.

[0047] Preparation Examples 1-6:

[0048] Preparation Example 1:

[0049] This preparation example provides a method for preparing a dopamine-modified polyethyleneimine interface reinforcing agent, including the following steps:

[0050] A 20 mmol / L tris(hydroxymethyl)aminomethane buffer solution was prepared, and the pH was adjusted to 8.0 with 1 mol / L sodium hydroxide solution. 15 g of branched polyethyleneimine aqueous solution was dissolved in 1000 mL of the buffer solution and magnetically stirred at room temperature until completely dissolved. 2 g of dopamine hydrochloride was slowly added to the solution, and the mixture was mechanically stirred at 20°C in the dark for 12 h under open-air conditions. After the reaction, the mixture was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in deionized water for 48 h. The dialyzed solution was freeze-dried for 48 h at -50°C and a vacuum of 5 Pa to obtain a dark brown dopamine-modified polyethyleneimine interface enhancer with a dopamine grafting rate of 8.0%.

[0051] Preparation Example 2:

[0052] This preparation example provides a method for preparing a dopamine-modified polyethyleneimine interface reinforcing agent, including the following steps:

[0053] A 20 mmol / L tris(hydroxymethyl)aminomethane buffer solution was prepared, and the pH was adjusted to 8.5 with 1 mol / L sodium hydroxide solution. 15 g of branched polyethyleneimine aqueous solution was dissolved in 1000 mL of the buffer solution and magnetically stirred at room temperature until completely dissolved. 4 g of dopamine hydrochloride was slowly added to the solution, and the mixture was mechanically stirred at 25°C in the dark for 18 h under open-air conditions. After the reaction, the mixture was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in deionized water for 48 h. The dialyzed solution was then freeze-dried for 48 h at -50°C and a vacuum of 5 Pa to obtain a dark brown dopamine-modified polyethyleneimine interface enhancer with a dopamine grafting rate of 10.5%.

[0054] Preparation Example 3:

[0055] This preparation example provides a method for preparing a dopamine-modified polyethyleneimine interface reinforcing agent, including the following steps:

[0056] A 20 mmol / L tris(hydroxymethyl)aminomethane buffer solution was prepared, and the pH was adjusted to 8.5 with 1 mol / L sodium hydroxide solution. 15 g of branched polyethyleneimine aqueous solution was dissolved in 1000 mL of the buffer solution and magnetically stirred at room temperature until completely dissolved. 6 g of dopamine hydrochloride was slowly added to the solution, and the reaction was carried out under open air at 30°C in the dark with mechanical stirring for 24 h. After the reaction, the mixture was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed in deionized water for 48 h. The dialyzed solution was then freeze-dried for 48 h at -50°C and a vacuum of 5 Pa to obtain a dark brown dopamine-modified polyethyleneimine interface enhancer, with a dopamine grafting rate of 12.0%.

[0057] Preparation Example 4:

[0058] This preparation example provides a method for preparing bamboo fiber ultrafine powder and a self-nucleation regulator, including the following steps:

[0059] Natural bamboo was mechanically de-greened and de-yellown, then crushed into 5mm pieces. These pieces were dried in a forced-air drying oven at 80℃ until the moisture content reached 1.5%. The dried bamboo pieces were then fed into a pulverizing system with a liquid nitrogen cooling jacket. Liquid nitrogen was introduced to control the internal temperature of the pulverizing chamber at -55℃, causing the bamboo pieces to enter a glassy state and undergo low-temperature embrittlement. The embrittled bamboo pieces were then fed into a fluidized bed impingement mill for ultrafine pulverization. By controlling the speed of the classifying wheel at 4500 rpm, ultrafine bamboo fiber powder was collected, with a particle size D50 of 5μm and an aspect ratio of 20. 100g of the prepared ultrafine bamboo fiber powder was dispersed in 1000mL of a 1% sodium hydroxide aqueous solution and mechanically stirred at 300rpm for 3 hours in a constant temperature water bath at 60℃. After filtration, the powder was washed with deionized water until the pH of the filtrate reached 7 and then dried. The washed powder was then immersed in a 1000 mL mixed solution of ethanol and water (9:1 volume ratio) containing 1 g of 3-aminopropyltriethoxysilane, and the hydrolysis reaction was carried out by stirring at room temperature for 4 h. After filtration, the powder was cured and dried in a vacuum drying oven at 100 °C for 12 h to obtain a nucleation regulator. The nucleation temperature at which it induces polymer crystallization was tested to be 125 °C.

[0060] Preparation Example 5:

[0061] This preparation example provides a method for preparing bamboo fiber ultrafine powder and a self-nucleation regulator, including the following steps:

[0062] Natural bamboo was mechanically de-greened and de-yellown, then crushed into 5mm pieces. These pieces were dried in a forced-air drying oven at 90℃ until the moisture content reached 1.0%. The dried bamboo pieces were then fed into a pulverizing system with a liquid nitrogen cooling jacket. Liquid nitrogen was introduced to control the internal temperature of the pulverizing chamber at -60℃, causing the bamboo pieces to enter a glassy state and undergo low-temperature embrittlement. The embrittled bamboo pieces were then passed through a fluidized bed impingement mill for ultrafine pulverization. By controlling the speed of the classifying wheel at 3000 rpm, ultrafine bamboo fiber powder was collected, with a particle size D50 of 8μm and an aspect ratio of 28. 100g of the prepared ultrafine bamboo fiber powder was dispersed in 1000mL of a 2% sodium hydroxide aqueous solution and mechanically stirred at 300 rpm for 2 hours in a constant temperature water bath at 70℃. After filtration, the powder was washed with deionized water until the pH of the filtrate reached 7 and then dried. The washed powder was then immersed in a 1000 mL mixed solution of ethanol and water (9:1 volume ratio) containing 2 g of 3-aminopropyltriethoxysilane, and the hydrolysis reaction was carried out by stirring at room temperature for 3 h. After filtration, the powder was cured and dried in a vacuum drying oven at 105 °C for 12 h to obtain a nucleation regulator. The nucleation temperature at which it induces polymer crystallization was tested to be 130 °C.

[0063] Preparation Example 6:

[0064] This preparation example provides a method for preparing bamboo fiber ultrafine powder and a self-nucleation regulator, including the following steps:

[0065] Natural bamboo was mechanically de-emulsified and crushed into 5mm pieces, then dried in a forced-air drying oven at 100℃ until the moisture content reached 0.5%. The dried bamboo pieces were then fed into a pulverizing system with a liquid nitrogen cooling jacket. Liquid nitrogen was introduced to control the internal temperature of the pulverizing chamber at -65℃, causing the bamboo pieces to enter a glassy state and undergo low-temperature embrittlement. The embrittled bamboo pieces were then fed into a fluidized bed impingement mill for ultrafine pulverization. By controlling the speed of the classifying wheel at 2000 rpm, ultrafine bamboo fiber powder was collected, with a particle size D50 of 20μm and an aspect ratio of 40. 100g of the prepared ultrafine bamboo fiber powder was dispersed in 1000mL of a 3% sodium hydroxide aqueous solution and mechanically stirred at 300 rpm for 1 hour in an 80℃ constant-temperature water bath. After filtration, the powder was washed with deionized water until the pH of the filtrate reached 7 and then dried. The washed powder was then immersed in a 1000 mL mixed solution of ethanol and water (9:1 volume ratio) containing 3 g of 3-aminopropyltriethoxysilane, and the hydrolysis reaction was carried out by stirring at room temperature for 2 h. After filtration, the powder was cured and dried in a vacuum drying oven at 110 °C for 12 h to obtain a nucleation regulator. The nucleation temperature at which it induces polymer crystallization was tested to be 135 °C.

[0066] Examples 1-8:

[0067] Example 1:

[0068] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0069] Polylactic acid and poly(dibutyl terephthalate) were mixed uniformly at a mass ratio of 7:3 to form a polyester matrix. A high-fiber masterbatch (i.e., the first masterbatch) was prepared by adding 79 parts by mass of the polyester matrix, 20 parts by mass of the bamboo fiber ultrafine powder obtained from Preparation Example 4, and 1 part by mass of the dopamine-modified polyethyleneimine interface reinforcing agent obtained from Preparation Example 1 into a co-rotating twin-screw extruder. The mixture was melt-blended, extruded, pelletized, and dried at a temperature of 150°C to 160°C. Simultaneously, 100 parts by mass of pure polyester matrix were prepared as a low-fiber masterbatch (i.e., the second masterbatch). The dried high-fiber and low-fiber masterbatches were melted separately through two single-screw extruders at 160°C. The two melt streams were fed into a multilayer co-extrusion distribution die to form an initial 5-layer alternating fluid. This fluid was then fed into a series-connected layer multiplier, which included a cutting and stacking unit operating at 150°C. After multiplication, 10 layers of melt were output. The multilayer melt extruded from the wide-slit die immediately enters the cooling system and is cooled and locked using a roller with a uniform temperature of 30°C. It is then output and wound up at a speed of 5 m / min by a traction device to obtain a biodegradable composite material with 10 layers and a fiber content gradient of 20% to 0% in the thickness direction.

[0070] Example 2:

[0071] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0072] Polylactic acid and poly(dibutyl terephthalate) were mixed uniformly at a mass ratio of 6:4 to form a polyester matrix. A high-fiber masterbatch (i.e., the first masterbatch) was prepared by co-blending and pelletizing 68.5 parts by mass of the polyester matrix, 30 parts by mass of the bamboo fiber ultrafine powder prepared in Preparation Example 5, and 1.5 parts by mass of the dopamine-modified polyethyleneimine interface reinforcing agent prepared in Preparation Example 2 in a twin-screw extruder. A low-fiber masterbatch (i.e., the second masterbatch) was prepared by co-blending and pelletizing 94.5 parts by mass of the polyester matrix, 5 parts by mass of the bamboo fiber ultrafine powder prepared in Preparation Example 5, and 0.5 parts by mass of the dopamine-modified polyethyleneimine interface reinforcing agent. The two masterbatches were melted separately in a single-screw extruder and fed into a multilayer co-extrusion die to form an initial 4-layer fluid. This fluid was then fed into a layer multiplier equipped with 4 cutting and stacking units at an operating temperature of 160°C, resulting in a 64-layer melt output after multiplication. After melt extrusion, the material is cooled and shaped by rollers at 40°C, and then wound up at a speed of 8m / min to obtain a biodegradable composite material with 64 layers and fiber content ranging from 30% to 5% in the thickness direction.

[0073] Example 3:

[0074] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0075] Polylactic acid (PLA) was used as the polyester matrix. A high-fiber masterbatch (i.e., the first masterbatch) was prepared by blending and pelletizing 58 parts by mass of the polyester matrix, 40 parts by mass of the bamboo fiber ultrafine powder obtained from Preparation Example 6, and 2 parts by mass of the dopamine-modified polyethyleneimine interface reinforcing agent obtained from Preparation Example 3. A low-fiber masterbatch (i.e., the second masterbatch) was prepared by blending and pelletizing 89 parts by mass of the polyester matrix, 10 parts by mass of the bamboo fiber ultrafine powder obtained from Preparation Example 6, and 1 part by mass of the dopamine-modified polyethyleneimine interface reinforcing agent. The two masterbatches were melted and fed into a multilayer co-extrusion die to form an initial 25-layer fluid. This fluid was then fed into a layer multiplier equipped with three cutting and stacking units, operating at 165°C, and after multiplication, output as a 200-layer melt. After the melt is extruded through a wide-slit die, it is cooled and shaped on a roller at 50°C, and then wound up at a speed of 10 m / min to obtain a biodegradable composite material with 200 layers and a fiber content gradient of 40% to 10% in the thickness direction.

[0076] Example 4:

[0077] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0078] Poly(butylene adipate) / terephthalate (PAT) was used as the polyester matrix. A foaming masterbatch (i.e., the first masterbatch) was prepared by blending 88 parts by weight of the polyester matrix, 10 parts by weight of the bamboo fiber ultrafine powder obtained from Preparation Example 5, 1 part by weight of azodicarbonamide, and 1 part by weight of nano-silica at 150°C and then pelletizing them for later use. Pure polyester matrix was used as the non-foaming masterbatch (i.e., the second masterbatch). The foaming masterbatch and the non-foaming masterbatch were melted in an extruder and fed into a multilayer co-extrusion die. Then, they passed through a layer multiplier containing four cutting and stacking units to form a 64-layer alternating melt. The melt was extruded through a wide-slit die, with the die temperature set at 165°C to decompose the foaming agent. The extruded foamed melt immediately entered an independently temperature-controlled gradient cooling roller system, where the roller temperature on one side in the thickness direction was set to a high temperature of 80°C, and the roller temperature on the other side was set to a low temperature of 50°C. Under the action of an asymmetric cooling field with a small temperature gradient, the moderate viscosity of the melt on the high-temperature side allows for bubble growth, while the rapid solidification of the melt on the low-temperature side inhibits foaming. Finally, the traction and winding process yields a biodegradable composite material with a continuous gradient of porosity from 30% to less than 5% in the thickness direction.

[0079] Example 5:

[0080] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0081] The same polyester matrix as in Example 4 was used. A foaming masterbatch (i.e., the first masterbatch) was prepared by blending and pelletizing 85 parts by weight of the polyester matrix, 10 parts by weight of the bamboo fiber ultrafine powder obtained in Preparation Example 5, 3 parts by weight of azodicarbonamide, and 2 parts by weight of nano-silica. A pure polyester matrix was used as the non-foaming masterbatch (i.e., the second masterbatch). The co-extrusion and layer multiplication process parameters were kept consistent with Example 4, resulting in a 64-layer melt. After extruding the melt through a 170°C wide-slit die, it immediately entered a gradient cooling roller system. The roller temperature on one side of the thickness direction was set to 120°C, and the roller temperature on the other side was set to 20°C. Under the rapid cooling field of the large temperature gradient, the bubbles on the high-temperature side fully expanded, and the melt on the low-temperature side instantly froze to form a dense skin. Finally, the melt was drawn and wound to obtain a biodegradable composite material with a continuous gradient of porosity from 70% to less than 5% in the thickness direction.

[0082] Example 6:

[0083] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0084] Polylactic acid (PLA) was used as the polyester matrix. A high-crystallinity masterbatch (i.e., the first masterbatch) was prepared by blending 99 parts by mass of the polyester matrix with 1 part by mass of the nucleating agent obtained from Preparation Example 4 at 160°C and then pelletizing for later use. Pure PLA without the nucleating agent was used as a low-crystallinity masterbatch (i.e., the second masterbatch). Both masterbatches were melt-fed into a multi-layer co-extrusion die via an extruder, and after processing through three layer multiplication units, 32 alternating layers of melt were output. The melt was extruded through a wide-slit die and entered a gradient cooling roller system. The roller temperature on one side of the thickness direction was set to 130°C to match the nucleation temperature of the nucleating agent in Preparation Example 4, while the roller temperature on the other side was set to 40°C. Maintaining a temperature of 130°C on the high-temperature side promoted rapid crystallization of PLA around the nucleating agent, while the low-temperature side achieved amorphous quenching, ultimately yielding a biodegradable composite material with a thickness-direction crystallinity gradient of 50% to 20%.

[0085] Example 7:

[0086] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0087] Polylactic acid (PLA) was used as the polyester matrix. A high-crystallinity masterbatch (i.e., the first masterbatch) was prepared by blending 97 parts by mass of the polyester matrix with 3 parts by mass of the nucleation regulator obtained from Preparation Example 6 and then pelletizing the mixture. Pure PLA was used as the low-crystallinity masterbatch (i.e., the second masterbatch). The melt co-extrusion and multiplication processes were the same as in Example 6. After melt extrusion, the mixture entered a gradient cooling roller system. The temperature of the high-temperature side roller was set to 135°C to match the nucleation temperature of the nucleation regulator in Preparation Example 6, and the temperature of the other side roller was set to 60°C. After locking the crystalline structure through an asymmetric thermodynamic field, a biodegradable composite material with a thickness-direction crystallinity gradient of 70% to 40% was finally obtained.

[0088] Example 8:

[0089] This embodiment provides a gradient structure biodegradable composite material and its preparation method, including the following steps:

[0090] Polylactic acid and poly(dibutyl terephthalate) were mixed at a mass ratio of 8:2 to form the polyester matrix. Composite functional masterbatch one (i.e., the first masterbatch) was prepared by blending and pelletizing 75 parts by mass of the polyester matrix, 20 parts by mass of the bamboo fiber ultrafine powder obtained from Preparation Example 5, 2 parts by mass of the self-nucleating regulator from Preparation Example 5, 1.5 parts by mass of the dopamine-modified polyethyleneimine interface reinforcing agent obtained from Preparation Example 2, and 1.5 parts by mass of azodicarbonamide. Composite functional masterbatch two (i.e., the second masterbatch) was prepared by blending and pelletizing 99.5 parts by mass of the polyester matrix and 0.5 parts by mass of the dopamine-modified polyethyleneimine interface reinforcing agent. The two masterbatch melts were fed into a multilayer co-extrusion die to form an initial 4-layer fluid. Through a layer multiplier consisting of 5 cutting and stacking units connected in series, 128 layers of melt were output at 165°C. After the melt is extruded through a 170°C wide-slit die to trigger foaming, it is immediately bonded to an asymmetric gradient cooling roller, with the high-temperature side roller at 130°C and the low-temperature side roller at 30°C. After winding, a three-dimensional gradient biodegradable composite material is obtained, which has gradients in fiber content, porosity, and crystallinity, and is cross-linked between layers by a network of covalent and hydrogen bonds.

[0091] Comparative Examples 1-5:

[0092] Comparative Example 1: Compared with Example 8, the difference is that without multi-layer co-extrusion and layer multiplication flow channel distribution, the prepared composite functional masterbatch one and composite functional masterbatch two are directly put into a single single screw extruder and mixed evenly in the same total mass ratio, and then directly extruded through a wide-slit die. Everything else is the same.

[0093] Comparative Example 2: Compared with Example 2, the difference is that after the two masterbatch melts are fed into the multilayer co-extrusion distribution die to form the initial 4-layer fluid, they are directly extruded from the wide-slit die and cooled without going through the layer multiplier for multiplication, resulting in a material with only a 4-layer structure, while the rest are the same.

[0094] Comparative Example 3: Compared with Example 2, the difference is that dopamine-modified polyethyleneimine interface reinforcing agent is not added in the formulation of both the high-fiber masterbatch and the low-fiber masterbatch. The missing mass fractions are made up with pure polyester matrix, and the rest are the same.

[0095] Comparative Example 4: Compared with Example 4, the difference is that the extruded foamed melt does not enter the independently temperature-controlled gradient cooling roller system, but enters the conventional uniform temperature cooling system. The temperature of the cooling rollers on both sides in the thickness direction is set to 50°C for uniform temperature cooling, and the rest are the same.

[0096] Comparative Example 5: Compared with Example 2, the difference is that when preparing the masterbatch, the bamboo fiber ultrafine powder with a specific aspect ratio prepared by low-temperature ultrafine grinding was replaced with commercially available ordinary raw bamboo powder with a conventional particle size of 50μm without any surface modification treatment; all other aspects were the same.

[0097] Test Example 1-3:

[0098] Test Example 1:

[0099] The composite materials prepared in Examples 2, 4, 6, and 8, as well as Comparative Examples 1 and 4, were selected as test subjects.

[0100] The sampled material was sliced ​​along its thickness direction. A high-precision slicer was used to uniformly divide the sample into five equal-thickness sections, labeled as section 1 to section 5. For the example sample, section 1 corresponds to the high-temperature cooling side during the preparation process, and section 5 corresponds to the low-temperature cooling side or quenching side; for the comparative sample, one side of the thickness direction was randomly assigned as section 1.

[0101] Fiber content distribution test: Approximately 5 to 10 mg of sliced ​​samples from each thickness range were placed in a platinum crucible of a thermogravimetric analyzer and heated from room temperature to 600°C at a constant heating rate of 10°C / min under a nitrogen protective atmosphere. Based on the difference in the thermal decomposition temperature ranges of bamboo fiber and polyester matrix at high temperatures, the true fiber mass fraction of different thickness ranges was calculated and recorded.

[0102] Porosity distribution testing: Bulk or thin film samples were immersed in liquid nitrogen for 5 minutes and then subjected to rapid brittle fracture to preserve the cross-sectional morphology. After vacuum sputtering with gold, the microscopic pore structure of each thickness range was observed using a scanning electron microscope (SEM). Binarization thresholding analysis was performed on the acquired SEM grayscale images of different regions using image processing software, and the average porosity area ratio of each range was statistically analyzed as the porosity test value for that range.

[0103] Crystallinity distribution test: Approximately 5 mg of sliced ​​film samples from each thickness range were taken and thermodynamically analyzed using a differential scanning calorimeter under nitrogen protection. The samples were heated to 200 °C at a heating rate of 10 °C / min, and the enthalpy of the melting endothermic peak was recorded by integration. Combined with the theoretical enthalpy of complete melting of the corresponding polyester matrix in a 100% crystalline state, the relative crystallinity of each thickness range was calculated.

[0104] Table 1. Distribution of structural parameters of composite materials in different thickness directions

[0105]

[0106] Summarize:

[0107] Based on the data in Table 1, combined with Figure 1 The content shows that the internal physical and chemical structure of materials in the thickness dimension exhibits spatial heterogeneity evolution. According to... Figure 1The porosity distribution trajectory shown reveals that the data curves for Examples 4 and 8, representing the gradient structure design, exhibit a clear monotonically decreasing trend. The porosity of Example 4 gradually decreases from approximately 31.2% at the high-temperature side of interval 1 to 3.1% in interval 5. Example 8, due to the use of a larger concentration of nucleating agent and foaming agent combined with a higher temperature difference, shows a steeper downward slope in its curve; the initial porosity in interval 1 reaches 68.7%, then rapidly decreases to 31.4% in interval 3, and bottoms out at 4.2% in interval 5. This contrasts sharply with the test data for Comparative Example 4, which shows... Figure 1 The surface appears as a nearly horizontal line, with the porosity of each interval fluctuating irregularly between 14.2% and 16.1%.

[0108] In the actual extrusion molding stage, the melt containing the foaming agent is in a thermodynamically unstable state as soon as it leaves the die. The temperature gradient applied along the thickness direction results in a moderate melt viscosity near the high-temperature roller, allowing the dissolved gas molecules sufficient time to relax, aggregate, nucleate, and expand over the interfacial tension between the two phases. Laboratory section observations confirmed that the bubble growth rate at this stage is much higher than the solidification rate of the polymer matrix. The melt near the low-temperature roller instantly crosses the glass transition or crystallization temperature, forcibly freezing the macromolecular chain segments. The rapidly increasing melt strength blocks the gas expansion path, thus preserving a dense, solid surface structure on a macroscopic scale. Comparative Example 4 removed this temperature gradient boundary condition, and the melt throughout the entire thickness dimension experienced a similar thermodynamic history, causing the originally discrete nucleation sites to evolve into a uniform foaming behavior.

[0109] Based on the chemical composition and crystalline state data in Table 1, Example 2 utilized multi-layer co-extrusion and layer multiplication channels to physically cut and rearrange the materials at the fluid dynamics level, transforming the set high and low concentration masterbatches into a continuous component distribution in space. The fiber mass fraction smoothly transitioned from 29.3% to 5.6%, breaking the conventional mixed form of approximately 17% homogeneous dispersion in Comparative Example 1. The same gradient mapping correlation was also found in the crystallinity test of Example 6. The polylactic acid molecular chains relied on the directionally introduced silane coupling to activate bamboo fibers as heterogeneous nucleation attachment points, retaining locally ordered orientation memory at a specific induction temperature on the high-temperature side, causing the crystallinity of interval 1 to climb to 48.9%. On the extremely low-temperature quenching side, the polymer chain segment arrangement process was forcibly interrupted, and the crystallinity was effectively suppressed at 21.3%. These interwoven test data verified that the construction of multi-dimensional gradient structures not only requires material distribution at the fluid dynamics level but also relies on the precise fixation of the phase transition process on a time scale by asymmetric heat transfer conditions.

[0110] Test Example 2:

[0111] The composite materials prepared in Examples 2, 3, and 8, as well as Comparative Examples 1, 2, 3, and 5, were selected as the experimental objects for mechanical testing.

[0112] In accordance with ISO 527 and ISO 178 standards, the block or sheet samples were cut into standard dumbbell-shaped tensile specimens and long strip-shaped bending specimens along the extrusion casting direction using a hydraulic punching machine. The cut specimens were then left to stand in a constant temperature and humidity environment of 23°C and 50% for 48 hours to eliminate residual internal stress.

[0113] Macroscopic mechanical properties were evaluated using a universal testing machine equipped with a high-precision extensometer. During tensile testing, the crosshead travel rate was set to 50 mm / min, and stress and strain data during the yielding and fracture processes were recorded in real time. Tensile strength and elongation at break were calculated. For the three-point bending test, the span was set to 40 mm, and the compression rate was 2 mm / min. Load-deflection curves were recorded, and the flexural modulus of the material was calculated. Each group of samples was tested in parallel five times, and the arithmetic mean was calculated to reduce dispersion error.

[0114] Interlayer bonding performance was evaluated for samples with multilayer structures. The material was cut into strips 15 mm wide and 150 mm long. A pre-opening operation was performed at the center of the thickness at one end of the sample using a blade, separating the upper and lower layers by approximately 20 mm. The separated ends were clamped in the upper and lower fixtures of a testing machine, and a T-peel test was performed at a speed of 100 mm / min. The average load during the stable peel phase was recorded and divided by the sample width to obtain the interlayer peel strength. For homogeneous materials where physical delamination is not possible, this test was skipped.

[0115] Table 2. Summary of test data on macroscopic mechanical and interfacial properties of composite materials

[0116]

[0117] Note: "-" indicates that the project cannot be tested or is not applicable (no data).

[0118] Summarize:

[0119] Based on the data in Table 2, combined with Figure 2 The content, the design of multi-scale gradient structures, reconciles the long-standing constraints between stiffness, strength and toughness of polymer composite materials at the macroscopic level. Observation Figure 2The spatial distribution trajectory of the scattered points in Example 1, due to the use of a conventional direct blending extrusion process, resulted in an irregular homogeneous dispersion of internal components. In the coordinate system, this dispersion was located in the lower left low-performance region, with tensile strength and elongation at break of only 31.5 MPa and 45.2%, respectively. The flexural modulus, indicated by the bubble area, was also only 1.95 GPa. In Examples 2, 3, and Example 8 (which incorporated multiple gradient designs), the data points shifted towards the upper right of the coordinate system, corresponding to substantial abrupt changes in mechanical parameters. Example 2 achieved a tensile strength of 45.3 MPa while extending the elongation at break to 112.4%. Example 3, relying on higher fiber and nucleating agent concentrations, increased the tensile strength to 52.7 MPa. Figure 2 The bubble area representing the flexural modulus also expanded, increasing to 3.41 GPa. Laboratory tensile fracture observation confirmed that the multilayered geometry with alternating thickness directions changed the crack propagation path, forcing the crack to deflect, bifurcate, or even passivate upon encountering interlayer boundaries, thus absorbing a large amount of deformation energy. The hard layer rich in bamboo fiber and with high crystallinity dominated the increase in modulus and yield stress, while the tough layer with low fiber content provided free volume for macromolecular chain rearrangement and slip, allowing the sample to maintain a long-term steady-state necking plastic rheology before fracture. When Comparative Example 5 was constructed using ordinary bamboo powder that had not undergone low-temperature embrittlement and silane activation, the data points dropped back to normal. Figure 2 The tensile strength of 25.6 MPa and the elongation at break of 33.8% in the lower left corner reveal the stress concentration and defect initiation problems caused by the rough filler inside the matrix.

[0120] While compressing the thickness of microlayers brings increased toughness, it often induces interlayer slippage failure, a potential engineering hazard. The test results of Comparative Example 3 confirm this conclusion; this group of samples had the dopamine-modified polyethyleneimine interfacial reinforcing agent removed, although... Figure 2The tensile strength and elongation at break, corresponding to the horizontal and vertical axes, remained at a respectable level of 41.2 MPa and 88.5%, respectively. However, the T-peel strength test value in Table 2 plummeted to 0.45 N / mm. The sample in Comparative Example 3 experienced large-area interlayer separation under slight shear force. Introducing modified macromolecules as an interfacial hinge network fundamentally reversed this situation. The peel load measured in Example 8 remained stable at a high level of 4.15 N / mm, while Examples 2 and 3 also reached 3.42 N / mm and 3.68 N / mm, respectively. Under the action of the high-temperature and high-shear flow field of melt extrusion, the active amine groups on the branched polyethyleneimine backbone initiated an interfacial transesterification reaction on the ester bonds on the polyester molecular chain. The grafted catechol groups anchored the cellulose interface through dense hydrogen bonds, and the covalent bond network spanning the phase boundary of the co-extruded layer suppressed macroscopic delamination failure. Comparative Example 2, obtained by reducing the number of flow channel distributions, had fewer layers and failed to advance the interface thickness to the optimal interlacing scale, resulting in a peel strength of only 1.85 N / mm. Tensile and bending data were also... Figure 2 The middle layer is located below the example cluster. This multi-dimensional performance comparison reveals the indispensable synergistic strengthening relationship between microscopic chemical crosslinking and mesoscopic physical layering in such systems.

[0121] Test Example 3:

[0122] The composite materials prepared in Examples 4, 5, and 8, as well as Comparative Examples 1 and 4, were selected as test objects for evaluating lightweighting, barrier properties, and degradation cycle.

[0123] According to ISO 1183 standard, the overall apparent density of samples is measured using the immersion method. A high-precision analytical balance equipped with a density testing component is used, with anhydrous ethanol as the immersion medium. The mass of the sample in air and in liquid environments is recorded separately. The apparent density of the material is obtained by buoyancy conversion, and this indicator is used to directly assess the material's lightweight level.

[0124] The barrier properties of materials were quantitatively characterized using an oxygen permeation meter based on the isobaric method and an infrared sensor-based moisture permeation meter. The effective test area was 50 cm². 2 Thin film or slice samples were loaded into the test chamber. Oxygen permeability was recorded at a test temperature of 23℃ and relative humidity of 50%, and moisture permeability was recorded at a test temperature of 38℃ and relative humidity of 90%. Different parts of each sample were selected for parallel testing three times, and the average value was calculated.

[0125] Degradation tests were conducted using simulated soil landfill conditions according to ISO 14855 standards. Samples were cut into 30mm x 30mm square slices, accurately weighed initially, and then buried in pre-prepared temperature- and humidity-controlled composting soil. The internal temperature of the composting chamber was controlled at 58℃, and the moisture content was maintained at approximately 50%. After a 90-day exposure period, the remaining samples were removed from the soil, ultrasonically cleaned with deionized water to remove adhering soil and microbial plaque, and then dried in a vacuum drying oven to constant weight. The degradation rate of the material under simulated natural conditions was evaluated by calculating the mass loss rate.

[0126] Table 3. Test data on lightweighting, barrier properties, and soil degradation of composite materials.

[0127]

[0128] Summarize:

[0129] Based on the data in Table 3, combined with Figure 3 The content states that the mutually exclusive bottleneck between lightweight structure and high barrier properties in conventional polymer processing technology is broken by asymmetric shaping methods. Figure 3 The distribution of each data point on the coordinate axis is shown in Comparative Example 1, which serves as a control group for unfoamed solid resin, and its apparent density is as high as 1.24 g / cm³. 3 Located at the right end of the coordinate system, the dense, continuous phase structure intercepts the permeation paths of most gas molecules, maintaining oxygen and moisture permeability at 88.6 cc / m³. 2 ·day and 10.1g / m 2 • The low position of day. When using a foaming process to try to reduce the material's self-weight, the disordered expansion of gas inside the matrix forms penetrating channels that usually destroy the original barrier layer. Comparative Example 4, where temperature gradient control was removed, exhibited typical structural collapse, with the density decreasing to 0.66 g / cm³. 3 At the same time, the bubble area representing the moisture permeability in the figure expands sharply, and the moisture permeability soars to 51.2 g / m². 2 The oxygen permeability is as high as 325.8cc / m³. 2 •day, thus losing its application basis in food preservation packaging or agricultural mulch film scenarios. The series of examples, by capturing the spatial differences in nucleation and growth, achieved microscopic morphological differentiation within the same block. Examples 4 and 5 controlled the density at 0.86 g / cm³, respectively. 3 and 0.63g / cm 3 The weight reduction target was successfully achieved, and the permeability data captured by the test probe did not show the expected exponential degradation. Example 8, in its fully functional state, achieved 0.78 g / cm³. 3 While maintaining a lightweight design, the oxygen permeability was effectively controlled at 104.2 cc / m³. 2·day, at Figure 3 The lower left corner occupies a region that balances multiple performance aspects. The superposition of high and low cross-linked layers, combined with the resin-enriched skin formed on the quenching side, forces oxygen and water vapor molecules to bypass the complex layered interfaces and microporous wall array. This extended labyrinth effect compensates for the material defects caused by the overall increase in porosity.

[0130] Shifting focus to the end of the material's lifespan, Table 3 records 90 days of soil burial mass loss data, revealing the regulatory mechanism of gradient configuration on the environmental degradation cycle. In Comparative Example 1, the dense state, lacking water infiltration channels, the microbial community could only initiate slow enzymatic decomposition from the outer surface of the sample, resulting in a mass loss rate of only 22.4% at the end of the test cycle. Examples 4 and 8 exhibited significant accelerated degradation characteristics of 41.2% and 52.7%, respectively. In the later stages of simulated soil burial, the high-porosity side of the composite material rapidly absorbed environmental moisture like a sponge, and the large internal surface area provided a vast breeding ground for fungi and actinomycetes. The hydrolysis reaction spread inward along the pre-designed low-crystallinity weak layer, subsequently eroding the bamboo fiber region anchored by the dopamine interface agent. The disintegration of hydrophilic fibers further tore apart the continuous polyester phase. This structure-driven environmental erosion path avoids the slow degradation process of traditional fully dense bio-based polymers in nature without compromising their physical functions during the service life.

Claims

1. A gradient-structured biodegradable composite material, characterized in that, The biodegradable composite material is formed by alternating layers of a first masterbatch and a second masterbatch to form a multilayer structure, and has at least one gradient structure selected from fiber content gradient, porosity gradient and crystallinity gradient in the thickness direction. The first masterbatch comprises the following raw materials in parts by weight: 58–99 parts of polyester matrix; Bamboo fiber ultrafine powder 0-40 parts; 0-2 parts of dopamine-modified polyethyleneimine interface reinforcing agent; 0-3 parts of self-nucleating regulator; Azodicarbonamide 0-3 parts; Nano silica 0-2 parts; In the first masterbatch, the weight parts of bamboo fiber ultrafine powder, self-nucleating regulator and azodicarbonamide are not all 0 parts at the same time; The second masterbatch comprises the following raw materials in parts by weight: 89-100 parts of polyester matrix; Bamboo fiber ultrafine powder 0-10 parts; 0-1 part of dopamine-modified polyethyleneimine interface reinforcing agent.

2. The gradient structure biodegradable composite material according to claim 1, characterized in that, The self-nucleation regulator is prepared by modifying the bamboo fiber ultrafine powder with a silane coupling agent, and the self-nucleation temperature of the polymer crystallization induced by the self-nucleation regulator is 125-135℃. The preparation method of the self-nucleating regulator includes: The bamboo fiber ultrafine powder was dispersed in a sodium hydroxide aqueous solution with a mass fraction of 1% to 3%, and mechanically stirred for 1 to 3 hours in a constant temperature water bath at 60 to 80°C. After filtration, washing and drying, the powder was then removed from the water. The dried bamboo fiber ultrafine powder was soaked in a mixed solution containing 3-aminopropyltriethoxysilane and stirred for 2-4 hours for hydrolysis. The self-nucleating regulator was then obtained by vacuum curing and drying. The bamboo fiber ultrafine powder has a particle size D50 of 5–20 μm and an aspect ratio of 20–40.

3. The gradient structure biodegradable composite material according to claim 1, characterized in that, The preparation method of the dopamine-modified polyethyleneimine interface reinforcing agent is as follows: A branched polyethyleneimine aqueous solution was dissolved in a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0–8.5, and dopamine hydrochloride was added. The mixture was mechanically stirred at 20–30°C in the dark for 12–24 h. After dialyzing, the mixture was freeze-dried at -50°C to obtain the dopamine-modified polyethyleneimine interface enhancer. The dopamine grafting rate of the dopamine-modified polyethyleneimine interface reinforcing agent is 8.0% to 12.0%.

4. The gradient structure biodegradable composite material according to claim 1, characterized in that, The polyester matrix is ​​polylactic acid, polybutylene adipate / terephthalate, or a mixture of the two; When it is a mixture, the mass ratio of polylactic acid to poly(adipate) / butyl terephthalate is (6-8):(2-4).

5. The gradient structure biodegradable composite material according to claim 1, characterized in that, The weight parts of each raw material in the first masterbatch are as follows: 75 parts polyester matrix, 20 parts bamboo fiber ultrafine powder, 2 parts self-nucleating regulator, 1.5 parts dopamine-modified polyethyleneimine interface reinforcing agent, and 1.5 parts azodicarbonamide; The weight parts of each raw material in the second masterbatch are as follows: 99.5 parts polyester matrix, 0.5 parts dopamine-modified polyethyleneimine interface reinforcing agent; The biodegradable composite material is a three-dimensional gradient composite material, which simultaneously possesses the fiber content gradient, the porosity gradient and the crystallinity gradient.

6. A method for preparing a gradient structure biodegradable composite material according to any one of claims 1-5, characterized in that, Includes the following steps: The first and second masterbatches, prepared separately, are melted in an extruder, and the two melts are fed into a multi-layer co-extrusion distribution die to form an initial multi-layer alternating fluid. The multilayer alternating fluid is fed into a layer multiplier equipped with 1 to 5 cutting and stacking units for multiplication processing, and the multiplied multilayer alternating melt is output. The multi-layered alternating melt, after being multiplied, is extruded through a wide-slit die and then cooled and shaped in a cooling system. It is then output and wound up by a traction device to obtain the gradient structure biodegradable composite material. The cooling and shaping process involves conventional cooling using rollers, or asymmetric cooling using an independently temperature-controlled gradient cooling roller system. When asymmetric cooling is performed, the temperature of the high-temperature side roller on one side of the thickness direction in the gradient cooling roller system is set to 80-135°C, and the temperature of the low-temperature side roller on the other side is set to 20-60°C.

7. The preparation method according to claim 6, characterized in that, The melt blending and extrusion temperature of the first masterbatch and the second masterbatch in the extruder is controlled at 150-160°C.

8. The preparation method according to claim 6, characterized in that, The operating temperature of the layer multiplier is 150–165°C; The number of layers in the output multilayer alternating melt is 10 to 200.

9. The preparation method according to claim 6, characterized in that, Before being prepared into the masterbatch, the bamboo fiber ultrafine powder undergoes the following pretreatment process: After being crushed and dried, natural bamboo is fed into a pulverizing system with a liquid nitrogen cooling jacket. The internal temperature of the pulverizing chamber is controlled at -65 to -55°C, causing it to enter the glassy state and undergo low-temperature embrittlement. Subsequently, it is passed into a fluidized bed impact jet mill, and the speed of the classifying wheel is controlled at 2000 to 4500 rpm for ultra-fine pulverization and collection.

10. The preparation method according to claim 6, characterized in that, When the first masterbatch contains azodicarbonamide, the extrusion temperature of the wide-slit die is set to 165-170°C.